2018
DOI: 10.1177/0306624x18763762
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Responsivity: Client Service Engagement in a Reentry Demonstration Program

Abstract: The specific responsivity principle advises us to provide offenders with treatment that takes into account their responsiveness to treatment, tied for example to their learning style, motivation, and gender. We examine challenges to service engagement and attendance in a community-based program in a reentry setting, and consider how far they correspond with these factors. Drawing on qualitative accounts of parolee engagement in services provided by parolees, service providers, case managers, and parole officer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The impact of competing demands (Richie, 2001). Logistical factors, scheduling difficulties, transportation (Sachs & Miller, 2018). Transportation (Walker et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of competing demands (Richie, 2001). Logistical factors, scheduling difficulties, transportation (Sachs & Miller, 2018). Transportation (Walker et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, formerly incarcerated persons are 3 times more likely to report unmet substance abuse treatment needs when compared with the general population (24% vs. 8.5%), and lack of financial resources is the most cited barrier to treatment among this population (Sung et al, 2011). In addition, approximately 17% of formerly incarcerated persons reported that they did not receive services because of lack of access to transportation or distance to treatment, a theme echoed in other studies of this type (Bohmert & DeMaris, 2018;Sachs & Miller, 2018;Spaulding et al, 2011). Health care needs are more pronounced for persons with lesser economic means (Porter & Novisky, 2017;Turney et al, 2012), and many formerly incarcerated persons do not have substantial economic and familial resources upon release (Middlemass, 2017).…”
Section: Literature Review Treatment Health Care and Access Barriersmentioning
confidence: 95%
“…Even more, many face stigma in finding employment, particularly people of color (Pager, 2003). Researchers also contend that treatment services may not be as responsive to the specific needs of individuals with a criminal conviction, like the trauma associated with incarceration and a reluctance to share personal problems, among other factors unique to this group (Belenko, 2006; Sachs & Miller, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the US, the Substance and Mental Health Administration (SAMHSA, 2014a) outlines four foundational principles-Recognize, Realize, Respond, and avoid Re-traumatizing-known as the "4 Rs of TIC." In a correctional context, these can be integrated into treatment as follows: (1) Recognize the high prevalence of trauma and adversity among clients in the criminal justice system (Jäggi et al, 2016;Martin et al, 2015;Pettus-Davis et al, 2019); (2) Realize the endless ways that trauma can stimulate criminogenic risk through its effect on self-regulation, neurocognitive functioning, and relational patterns (Ardino, 2012;Cheng et al, 2019;Holley et al, 2017;van der Kolk, 2006;Wojciechowski, 2020); (3) Respond to client needs by understanding trauma and providing trauma-responsive interventions (Pettus-Davis et al, 2019); and (4) Avoid re-traumatizing clients with harsh confrontational and punitive approaches that fail to support client well-being and model empathy and respect (Blagden et al, 2016;Sachs & Miller, 2018;Stinson & Clark, 2017;Sturgess et al, 2016).…”
Section: Trauma-informed Care and Criminal Justicementioning
confidence: 99%
“…It does not replace the evidence-based cognitive-behavioral interventions we are familiar with, but rather it provides a strengths-based framework for delivering those interventions in a way that maximizes client selfdetermination, locus of control, and personal ownership of change. Frontline workers in the justice system have an opportunity to engage with correctional clients using trauma-informed practices that reduce barriers, encourage accountability, and support reintegration and rehabilitation (Sachs & Miller, 2018). Such practices can enhance the likelihood of reduced recidivism by building adaptive skills for resilience and post-traumatic growth.…”
Section: Useful Questions For Professionals and Organizations Interested In Implementing Ticmentioning
confidence: 99%